A cutting tool with a high-hardness self-lubricating coating and a preparation method thereof
By adopting a multi-layered TiAlN coating design and preparing with CVD technology, the existing coating is easily peeled off at high temperatures, achieving high hardness and self-lubricating effects, and extending the service life of the tool.
Patent Information
- Application Number
- CN202510051347.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-13
AI Technical Summary
The existing TiAlN coating is prone to coating peeling at high temperatures, resulting in a shortening of the tool service life.
The coating design with a multi-layer structure, including the first subcoat Ti1-xAlxN, the second subcoat TiaAlbSicN, the third subcoat TihAliSijBkN1-k, and the first gradient layer TiAlSiN and the second gradient layer TiAlSiBN, were prepared by chemical vapor deposition (CVD) technology.
It significantly improves the hardness and bonding force of the coating, reduces the risk of coating peeling, and extends the service life of the tool.
Smart Images

Figure CN119491200B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coated tool technology, and in particular relates to a cutting tool with a high-hardness self-lubricating coating and a preparation method thereof. Background Art
[0002] Modern manufacturing is developing towards high efficiency and environmental protection. High-speed and dry cutting accounts for an increasing proportion. During dry cutting, the local temperature of the tool tip can reach thousands of degrees, which greatly increases tool wear. Ordinary carbide tools can no longer meet the development trend of modern manufacturing. Therefore, various high-temperature resistant and high-oxidation-resistant materials have been developed and successfully applied to modern manufacturing.
[0003] In recent years, the ultra-hard TiAlN coating material has developed rapidly. Its good wear resistance and high temperature oxidation resistance have made it successfully applied to cemented carbide tools. In order to further improve its performance, at least one alloying element (Si, B, Cr, etc.) is usually added during the deposition of TiAlN coating by physical vapor deposition (PVD) to form a multi-element transition metal nitride of the Ti-Al-XN type, which can significantly improve the wear resistance and high temperature oxidation resistance of the original TiAlN coating.
[0004] With the development of industrial technology, TiAlN coatings, which were originally only prepared on PVD (physical vapor deposition), can now be achieved using CVD coating technology. Unlike the PVD method, the Al content of TiAlN coatings prepared by CVD can exceed 70%, and they have higher oxidation resistance. With the deepening of technology, the research on doping of CVD TiAlN coatings has become more and more extensive. Studies have shown that the TiAlSiN coating prepared by CVD method can significantly improve the wear resistance of TiAlN coatings. On the basis of TiAlSiN coatings, the TiAlSiBN coatings formed by adding B elements have further improved wear resistance and high-temperature oxidation resistance. B elements can effectively inhibit the affinity of other elements in the coating with the processing material, hinder the diffusion of the coating and the material, and provide better self-lubrication. Single-layer TiAlN, TiAlSiN or TiAlSiBN coatings cannot play a good role in protecting the tool. The preparation of multi-layer TiAlN / TiAlSiN / TiAlSiBN coatings has better comprehensive performance than single-layer coatings. However, due to the large internal stress between the coatings, the bonding force between the coatings is low, and the coatings are prone to peeling during processing, affecting the service life of the tool. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the main purpose of the present invention is to provide a cutting tool with a high-hardness self-lubricating coating and a preparation method thereof.
[0006] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:
[0007] A cutting tool with a high-hardness self-lubricating coating, comprising:
[0008] A tool substrate and a coating formed on the tool substrate;
[0009] The coating has a multi-layer structure, which includes, from the inside to the outside, a first sub-coating, a first gradient layer, a second sub-coating, a second gradient layer and a third sub-coating;
[0010] The first sub-coating is Ti 1-x Al x N layers, where 0.6≤x≤0.8;
[0011] The second sub-coating is Ti a Al b Si c N layers, where a+b+c=1, 0.3≤a≤0.6, 0.4≤b≤0.6, 0≤c≤0.1;
[0012] The third sub-coating is Ti h Al i Si j B k N 1-k Layer, where h+i+j=1, 0.35≤h≤0.55, 0.40≤i≤0.55, 0≤j≤0.1, 0≤k≤0.05;
[0013] The first gradient layer is a TiAlSiN layer, wherein the Si content in the first gradient layer increases gradually from the inside to the outside and is not higher than the Si content in the second sub-coating layer;
[0014] The second gradient layer is a TiAlSiBN layer, wherein the B content in the second gradient layer increases in a gradient from the inside to the outside and is not higher than the B content in the third sub-coating.
[0015] As a preferred embodiment of the cutting tool with a high-hardness self-lubricating coating described in the present invention, the first sub-coating mainly comprises a face-centered cubic crystal structure fcc, wherein the volume fraction of the face-centered cubic crystal structure fcc is not less than 80%.
[0016] As a preferred embodiment of the cutting tool with a high hardness self-lubricating coating described in the present invention, the second sub-coating comprises face-centered cubic phase fcc-TiN, face-centered cubic phase fcc-AlN, close-packed hexagonal phase hcp-AlN and amorphous phase a-Si3N4, wherein the volume fraction of the face-centered cubic phase fcc-AlN is not less than 60%.
[0017] As a preferred embodiment of the cutting tool with a high-hardness self-lubricating coating described in the present invention, the atomic content of Si in the second sub-coating is not higher than 10%, preferably 10%; the atomic ratio of Ti / Al in the second sub-coating is 0.5~1.3.
[0018] As a preferred embodiment of the cutting tool with a high-hardness self-lubricating coating according to the present invention, the third sub-coating comprises nanocrystalline TiAlBN and amorphous SiB m N n , with amorphous SiB m N n The morphology of encapsulated nanocrystalline TiAlBN coexists, wherein the grain size of the nanocrystalline TiAlBN is ≤30nm.
[0019] As a preferred embodiment of the cutting tool with a high-hardness self-lubricating coating described in the present invention, the atomic content of B in the third sub-coating is not higher than 5%, preferably 5%; the atomic ratio of Ti, Al and Si in the third sub-coating is 50:40:10.
[0020] As a preferred embodiment of the cutting tool with a high-hardness self-lubricating coating described in the present invention, the total thickness of the coating is 6-25 μm.
[0021] As a preferred embodiment of the cutting tool with a high hardness self-lubricating coating described in the present invention, the thickness of the first sub-coating is 3~8μm, preferably 5~6μm; the thickness of the second sub-coating is 1~5μm, preferably 1~3μm; the thickness of the third sub-coating is 1~5μm, preferably 1~3μm; the thickness of the first gradient layer and the second gradient layer are both 0.5~2μm.
[0022] As a preferred embodiment of the cutting tool with a high-hardness self-lubricating coating described in the present invention, the coating further includes a primer layer adjacent to the surface of the tool substrate and an outermost colored layer, the primer layer and the colored layer are respectively composed of at least one of Ti, TiN, TiC, and TiCN, wherein the thickness of the primer layer is 0.1~0.5μm, and the thickness of the colored layer is 0.1~2μm.
[0023] As a preferred embodiment of the cutting tool with a high-hardness self-lubricating coating described in the present invention, the coating is deposited by chemical vapor deposition (CVD).
[0024] As a preferred embodiment of the cutting tool with a high-hardness self-lubricating coating described in the present invention, the critical load LC of the bonding strength of the coating is greater than 100N, and the absolute value of the residual stress is greater than 1500MPa.
[0025] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:
[0026] A method for preparing the above-mentioned cutting tool with a high-hardness self-lubricating coating comprises the following steps:
[0027] S1: The first sub-coating is obtained by chemical reaction using chemical vapor deposition technology at 700-900°C and 6-20mbar with H2, TiCl4, AlCl3, and NH3 as raw materials;
[0028] S2: Using chemical vapor deposition technology, at 700-900°C and 6-20 mbar, using H2, TiCl4, SiCl4, AlCl3, and NH3 as raw materials, gradually increasing the flow rate of SiCl4, and obtaining the first gradient layer through chemical reaction;
[0029] S3: The second sub-coating is obtained by chemical reaction using chemical vapor deposition technology at 700~900℃ and 6~20mbar with H2, TiCl4, SiCl4, AlCl3 and NH3 as raw materials;
[0030] S4: Using chemical vapor deposition technology, at 700~900℃, 6~20mbar, with H2, TiCl4, SiCl4, BCl3, AlCl3, NH3 as raw materials, Ar as carrier gas, and gradually increasing the flow rate of BCl3, the second gradient layer is obtained by chemical reaction;
[0031] S5: The third sub-coating is obtained by chemical reaction using chemical vapor deposition technology at 700~900℃ and 6~20mbar with H2, TiCl4, SiCl4, BCl3, AlCl3, NH3 as raw materials and Ar as carrier gas.
[0032] The beneficial effects of the present invention are as follows:
[0033] The present invention provides a cutting tool with a high-hardness self-lubricating coating and a preparation method thereof, which has the following advantages:
[0034] (1) The present invention adopts CVD technology to prepare the first sub-coating, the second sub-coating and the third sub-coating. Compared with the coating prepared by PVD, the first sub-coating, the second sub-coating and the third sub-coating have a higher aluminum content and less hcp-AlN phase, thereby giving the coating a higher hardness.
[0035] (2) The first gradient layer and the second gradient layer in the present invention not only avoid the large residual stress caused by the difference in material properties through the gradient change of Si and B content, but also promote the formation of coherent interfaces between the gradient layer and each sub-coating, thereby significantly enhancing the bonding force between the coatings.
[0036] (3) In the present invention, Si element is doped on the basis of CVD TiAlN, and the crystal structure of the coating is gradually transformed from cubic B1-NaCl type to hexagonal A1B2 type structure, which can refine the coating grains and produce a smaller grain size distribution, thereby improving the bonding strength and fracture toughness.
[0037] (4) The present invention dopes B element on the basis of CVD TiAlSiN, which can inhibit the affinity of other elements in the coating with the material, effectively hinder the diffusion of the coating into the material, increase the self-lubricating effect of the coating, and reduce the chip nodules on the surface of the tool.
[0038] (5) The present invention limits the atomic ratio of each element in the first sub-coating, the second sub-coating and the third sub-coating in the multi-layer coating, so that the coating has better hardness and high temperature oxidation resistance within this range.
[0039] (6) The first sub-coating TiAlN layer in the present invention is mainly a face-centered cubic crystal structure (fcc), and its volume fraction is not less than 80%. This crystal structure not only improves the hardness and wear resistance of the coating, but also enhances its corrosion resistance and fatigue resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0041] Figure 1 It is a schematic cross-sectional view of the tool of the present invention.
[0042] Figure 2 This is a scratch test diagram of the bonding strength between the tool substrate and the coating in Example 1 of the present invention.
[0043] Figure 3 This is a scratch test diagram of the bonding strength between the tool substrate and the coating of Comparative Example 1 of the present invention.
[0044] Among them, 1 is a tool substrate, 2 is a coating, 21 is a base layer, 22 is a first sub-coating, 23 is a first gradient layer, 24 is a second sub-coating, 25 is a second gradient layer, 26 is a third sub-coating, and 27 is a coloring layer.
[0045] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0046] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0047] like Figure 1 As shown, the present invention provides a cutting tool with a high-hardness self-lubricating coating and a preparation method thereof. The cutting tool with a high-hardness self-lubricating coating comprises:
[0048] A tool substrate 1 and a coating 2 formed on the tool substrate 1;
[0049] The coating has a multi-layer structure, including, from the inside to the outside, a first sub-coating 22, a first gradient layer 23, a second sub-coating 24, a second gradient layer 25 and a third sub-coating 26;
[0050] The first sub-coating layer 22 is Ti 1-x Al x N layers, wherein 0.6≤x≤0.8; specifically, x may be, for example, any one of 0.6, 0.65, 0.7, 0.75, 0.8, or a range between any two thereof;
[0051] The second sub-coating layer 24 is Ti a Al b Si c N layers, wherein a+b+c=1, 0.3≤a≤0.6, 0.4≤b≤0.6, 0≤c≤0.1; specifically, a may be, for example, any one of 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6 or a range between any two of them; b may be, for example, any one of 0.4, 0.45, 0.5, 0.55, 0.6 or a range between any two of them; c may be, for example, any one of 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or a range between any two of them;
[0052] The third sub-coating 26 is Ti h Al i Si j B k N 1-klayer, wherein h+i+j=1, 0.35≤h≤0.55, 0.40≤i≤0.55, 0≤j≤0.1, 0≤k≤0.05; specifically, h can be, for example, any one of 0.35, 0.4, 0.45, 0.5, 0.55 or a range between any two of them; i can be, for example, any one of 0.4, 0.45, 0.5, 0.55 or a range between any two of them; j can be, for example, any one of 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1 or a range between any two of them; k can be, for example, any one of 0, 0.01, 0.02, 0.03, 0.04, 0.05 or a range between any two of them;
[0053] The first gradient layer 23 is a TiAlSiN layer, wherein the Si content in the first gradient layer 23 increases in a gradient from the inside to the outside and is not higher than the Si content in the second sub-coating layer;
[0054] The second gradient layer 25 is a TiAlSiBN layer, wherein the content of B in the second gradient layer 25 increases in a gradient from the inside to the outside and is not higher than the content of B in the third sub-coating layer.
[0055] Preferably, the first sub-coating 22 mainly comprises a face-centered cubic crystal structure fcc, wherein the volume fraction of the face-centered cubic crystal structure fcc is not less than 80%. The thickness of the first sub-coating 22 is 3-8 μm, preferably 5-6 μm.
[0056] Preferably, the second sub-coating 24 comprises face-centered cubic phase fcc-TiN, face-centered cubic phase fcc-AlN, close-packed hexagonal phase hcp-AlN and amorphous phase a-Si3N4, wherein the volume fraction of face-centered cubic phase fcc-AlN is not less than 60%; the atomic content of Si in the second sub-coating 24 is not higher than 10%, preferably 10%; the atomic ratio of Ti / Al in the second sub-coating 24 is 0.5-1.3. The thickness of the second sub-coating is 1-5 μm, preferably 1-3 μm.
[0057] Preferably, the third sub-coating 26 comprises nanocrystalline TiAlBN and amorphous SiB m N n , with amorphous SiB m N n The morphology of the nanocrystalline TiAlBN coexists, wherein the grain size of the nanocrystalline TiAlBN is ≤30nm. The thickness of the third sub-coating 26 is 1-5μm, preferably 1-3μm. The atomic content of B in the third sub-coating 26 is not higher than 5%, preferably 5%; the atomic ratio of Ti, Al, and Si in the third sub-coating 26 is 50:40:10.
[0058] Preferably, the total thickness of the coating is 6-25 μm.
[0059] Preferably, the thickness of the first gradient layer 23 and the second gradient layer 25 are both 0.5-2 μm.
[0060] Preferably, the coating 2 also includes a base layer 21 adjacent to the surface of the tool substrate 1 and an outermost colored layer 27 (the colored layer 27 located outside the third sub-coating 26 and the outermost colored layer 27 of the coating 2), the base layer 21 and the colored layer 27 are respectively composed of at least one of Ti, TiN, TiC, and TiCN, wherein the thickness of the base layer 21 is 0.1~0.5μm, preferably 0.2~0.4μm; the thickness of the colored layer 27 is 0.1~2μm, preferably 0.2~1.5μm.
[0061] Preferably, the coating 2 is deposited by chemical vapor deposition (CVD).
[0062] Preferably, the critical load LC of the bonding strength of the coating 2 is greater than 100 N, and the absolute value of the residual stress is greater than 1500 MPa.
[0063] The method for preparing the cutting tool comprises the following steps:
[0064] S1: A first sub-coating 22 is obtained by chemical reaction using H2, TiCl4, AlCl3, and NH3 as raw materials at 700-900°C and 6-20 mbar using chemical vapor deposition technology;
[0065] S2: using chemical vapor deposition technology, at 700-900°C and 6-20 mbar, using H2, TiCl4, SiCl4, AlCl3, and NH3 as raw materials, gradually increasing the flow rate of SiCl4, and obtaining the first gradient layer 23 through chemical reaction;
[0066] S3: A second sub-coating 24 is obtained by chemical reaction using H2, TiCl4, SiCl4, AlCl3, and NH3 as raw materials at 700-900°C and 6-20 mbar using chemical vapor deposition technology;
[0067] S4: using chemical vapor deposition technology, at 700-900°C and 6-20 mbar, using H2, TiCl4, SiCl4, BCl3, AlCl3, and NH3 as raw materials, Ar as carrier gas, and gradually increasing the flow rate of BCl3, to obtain the second gradient layer 25 through chemical reaction;
[0068] S5: The third sub-coating 26 is obtained by chemical reaction using chemical vapor deposition technology at 700~900℃ and 6~20mbar with H2, TiCl4, SiCl4, BCl3, AlCl3, NH3 as raw materials and Ar as carrier gas.
[0069] Preferably, the base layer 21 and the coloring layer 27 are deposited by a CVD method, the reaction conditions are 700-900° C., 6-20 mbar, and TiCl 4 , N 2 and H 2 are used as raw materials.
[0070] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0071] Example 1
[0072] A method for preparing a cutting tool having a high-hardness self-lubricating coating, comprising:
[0073] The substrate was prepared using the following process parameters: the cemented carbide composition was 9wt% Co, 2wt% cubic carbide and the remainder WC, and the tool model was RPHT 1204M8E-MM3.
[0074] The base layer and the coloring layer are both TiN, and the multi-layer coating structure is base layer TiN + first sub-coating Ti 0.2 Al 0.8 N+first gradient layer TiAlSiN+second sub-coating Ti 0.3 Al 0.6 Si 0.1 N+second gradient layer TiAlSiBN+third sub-coating Ti 0.4 Al 0.5 Si 0.1 B 0.05 N 0.95 + Coloring layer TiN.
[0075] In a specific example, the coating of the first gradient layer TiAlSiN and the second gradient layer TiAlSiBN of the coating 2 of the cutting tool is prepared using the process parameters in Tables 1 and 2 as Example 1, and Comparative Example 1 does not have the first gradient layer TiAlSiN and the second gradient layer TiAlSiBN, and the remaining coating process parameters are the same as those of Example 1. The coating thickness of the first gradient layer TiAlSiN and the second gradient layer TiAlSiBN is about 1.0 μm.
[0076] Table 1 Process parameters of the first gradient layer TiAlSiN
[0077]
[0078] Table 2 Process parameters of the second gradient layer TiAlSiBN
[0079]
[0080] The REVETEST scratch tester produced by CSM of Switzerland was used to measure the bonding strength between the coating and the substrate. The scratch test method is to use a hemispherical diamond indenter with a diameter of about 200 microns to slide on the coating surface. During this process, the vertical load L is continuously increased by the automatic loading mechanism. When L reaches its critical load LC, the coating and the substrate begin to peel off. The critical load LC of the interface between the coating and the substrate is the minimum load required for the indenter to completely scratch the coating and continuously peel it from its substrate; at the same time, the friction F between the indenter and the coating and the substrate changes accordingly. At this time, the coating will produce acoustic emission. The acoustic emission signal, the change in load, and the change in tangential force during the scratch are obtained by the sensor. After amplification, the measurement results are input into the computer and plotted into a graph through A / D conversion. The acoustic emission peak is obtained at the critical load value LC on the acoustic emission signal-load curve. At this time, the critical load LC is the criterion for the bonding strength between the coating and the substrate. The bonding strength between the coating and the substrate of the tools in Example 1 and Comparative Example 1 is shown in Table 3, and the scratch test graphs are shown in Table 3. Figure 2 , 3 shown.
[0081] Table 3 Bonding strength between the coating and the substrate of Example 1 and Comparative Example 1
[0082]
[0083] It can be seen from Table 3 that the bonding strength of the multilayer coating prepared in Example 1 of the present invention is significantly higher than that of Comparative Example 1 without a transition layer, indicating that the multilayer coating tool provided by the present invention has better bonding strength than the prior art.
[0084] Example 2
[0085] A method for preparing a cutting tool having a high-hardness self-lubricating coating, comprising:
[0086] The substrate was prepared using the following process parameters: the cemented carbide composition was 9wt% Co, 2wt% cubic carbide and the remainder WC, and the tool model was RPHT 1204M8E-MM3.
[0087] The base coating of Example 2 is TiN, and the first sub-coating is Ti 0.2 Al 0.8 N, the first gradient layer is TiAlSiN, the Si content is between 0 and 10at%, and the second sub-coating is Ti 0.3 Al 0.6 Si 0.1 N, the second gradient layer is TiAlSiBN, the B content is between 0 and 5 at%, and the third sub-coating is Ti 0.4Al 0.5 Si 0.1 B 0.05 N 0.95 , the preparation method of each layer is as follows:
[0088] 1) TiN base layer, deposition temperature 850℃, deposition pressure 120mbar, reaction gas TiCl4, N2 and H2, deposition time 80min, coating thickness 0.5μm;
[0089] 2) First sub-coating Ti 0.2 Al 0.8 N, deposition temperature 700 ° C, deposition pressure 12 mbar, reaction gases are TiCl4, AlCl3, NH3 and H2, deposition time 150 min, coating thickness 5 μm;
[0090] 3) The first gradient layer TiAlSiN, the deposition temperature is 700℃, the deposition pressure is 12mbar, the reaction gases are TiCl4, AlCl3, NH3, SiCl4 and H2, the proportion of SiCl4 gradually increases, the deposition time is 30min, and the coating thickness is 1μm;
[0091] 4) Second sub-coating Ti 0.3 Al 0.6 Si 0.1 N, deposition temperature 700℃, deposition pressure 12mbar, reaction gases are TiCl4, AlCl3, NH3, SiCl4 and H2, deposition time 130min, coating thickness 5μm;
[0092] 5) The second gradient layer TiAlSiBN, deposition temperature 700 ° C, deposition pressure 12mbar, reaction gas is TiCl4, AlCl3, NH3, SiCl4, BCl3 and H2, Ar is the carrier gas, the proportion of BCl3 gradually increases, deposition time 25min, coating thickness 1μm;
[0093] 6) The third sub-coating Ti 0.4 Al 0.5 Si 0.1 B 0.05 N 0.95 , deposition temperature 700℃, deposition pressure 12mbar, reaction gases are TiCl4, AlCl3, NH3, SiCl4, BCl3 and H2, Ar is the carrier gas, deposition time is 120min, and coating thickness is 5μm.
[0094] The purity of the above reaction gases is required to be greater than 95%, preferably 99.99%.
[0095] The coating structure of Comparative Example 2 is TiN+Ti 0.2 Al0.8 N+ gradient layer TiAlSiN (Si content between 0 and 10 at%) + Ti 0.3 Al 0.6 Si 0.1 N. The preparation method of each layer is as follows:
[0096] 1) TiN base layer, deposition temperature 850℃, deposition pressure 120mbar, reaction gas TiCl4, N2 and H2, deposition time 80min, coating thickness 0.5μm;
[0097] 2) First sub-coating Ti 0.2 Al 0.8 N, deposition temperature 700 ° C, deposition pressure 12 mbar, reaction gases TiCl4, AlCl3, NH3 and H2, deposition time 150 min, coating thickness 5 μm;
[0098] 3) Gradient layer TiAlSiN, deposition temperature 700℃, deposition pressure 12mbar, reaction gases TiCl4, AlCl3, NH3, SiCl4 and H2, the proportion of SiCl4 gradually increased, deposition time 30min, coating thickness 1μm;
[0099] 4) Second sub-coating Ti 0.3 Al 0.6 Si 0.1 N, deposition temperature 700℃, deposition pressure 12mbar, reaction gases TiCl4, AlCl3, NH3, SiCl4 and H2, deposition time 260min, coating thickness 10μm.
[0100] The coating structure of Comparative Example 3 is Ti 0.4 Al 0.5 N+Ti 0.4 Al 0.5 Si 0.1 N+Ti 0.4 Al 0.5 Si 0.1 B 0.05 N 0.95 The preparation method of each layer using PVD method is as follows:
[0101] 1) First sub-coating Ti 0.4 Al 0.5 N, using alloy target Ti / Al=35 / 65, deposition temperature 600℃, deposition pressure 7.5×10 -2 mbar, purity 99.99% N2, deposition time 1h;
[0102] 2) Second sub-coating Ti 0.4 Al 0.5 Si0.1 N, alloy target material Ti / Al / Si=40 / 50 / 10, deposition temperature 600℃, deposition pressure 7.5×10 -2 mbar, purity 99.99%N 2, Sedimentation time 1.5h;
[0103] 3) The third sub-coating Ti 0.4 Al 0.5 Si 0.1 B 0.05 N 0.95 , alloy targets Ti / Al / B=40 / 50 / 10 and Ti / Si=60 / 40 were used, deposition temperature was 600°C, and deposition pressure was 7.5×10 -2 mbar, purity 99.99% N2, deposition time 2h.
[0104] The residual stress of the coating was measured using a D8 ADVANCE X-ray diffractometer produced by Bruker, Germany. When residual stress exists in the coating, the inter-crystalline spacing will change. When Bragg diffraction occurs, the diffraction peak position 2θ will also change accordingly. The commonly used method for measuring residual stress in coatings is the tilt method, which is to adjust the crystal plane azimuth angle Ψ by rotating the horizontal axis of the X-ray diffractometer sample stage, set multiple crystal plane azimuth angles Ψ, and scan a certain {hkl} diffraction peak of the selected coating at each crystal plane azimuth Ψ. By measuring the peak position 2θ of the {hkl} diffraction peak of the coating corresponding to each crystal plane azimuth Ψ, the relationship between 2θ and sin 2 The slope M of ψ is used to find the elastic modulus E and Poisson's ratio μ of the coating, and K can be calculated. Then, K can be substituted into the residual stress expression to calculate the residual stress value of the coating. The stress and oxidation resistance comparison of the coatings of Example 2, Comparative Example 2 and Comparative Example 3 are shown in Table 4.
[0105] Table 4 Comparison of coating stress and oxidation resistance of Example 2, Comparative Example 2 and Comparative Example 3
[0106]
[0107] It can be seen from Table 4 that the multilayer coating prepared by Example 2 of the present invention has a high coating stress. The greater the coating stress, the more conducive it is to inhibiting the generation of thermal cracks during the cutting process and reducing the risk of coating peeling during the cutting process, thereby improving the cutting performance. At the same time, it has higher high-temperature oxidation resistance than the coating prepared by the existing coating technology.
[0108] The cutting comparison of the tools of Example 2, Comparative Example 2 and Comparative Example 3 is shown in Table 5. The cutting conditions are: Vc=150m / min, fz=0.22mm / t, ap=2.5mm, ae=75mm; the cutting material is: titanium alloy TC18, dry cutting.
[0109] Table 5 Comparison of cutting life of the tools in Example 2, Comparative Example 2 and Comparative Example 3
[0110]
[0111] It can be seen from Table 5 that the multilayer coating prepared by the method of the present invention has greatly improved wear resistance compared with the existing coating technology.
[0112] The surface area of the cutting edge of the cutting test samples of Example 2, Comparative Example 2 and Comparative Example 3 was calculated, and the cutting conditions were: Vc=150m / min, fz=0.22mm / t, ap=2.5mm, ae=75mm; the cutting material was: titanium alloy TC18, dry cutting. The results are shown in Table 6.
[0113] Table 6 Cutting test sample area of Example 2, Comparative Example 2 and Comparative Example 3
[0114]
[0115] It can be seen from Table 6 that the surface layer of the multilayer coating prepared by the method of the present invention has obvious self-lubricating properties, which can well inhibit the affinity between the workpiece material and the tool surface, reduce adhesive wear, and thus improve the tool life.
[0116] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A cutting tool having a high hardness self-lubricating coating, characterized in that: include: A tool substrate and a coating formed on the tool substrate; The coating has a multi-layer structure, which includes, from the inside to the outside, a first sub-coating, a first gradient layer, a second sub-coating, a second gradient layer and a third sub-coating; The first sub-coating is Ti 1-x Al x N layers, wherein 0.6≤x≤0.8; the volume fraction of the face-centered cubic crystal structure of the first sub-coating is not less than 80%; The second sub-coating is Ti a Al b Si c N layers, where a+b+c=1, 0.3≤a<0.6, 0.4≤b≤0.6, 0 <c≤0.1; The third sub-coating is Ti h Al i Si j B k N 1-k layer, where h + i + j = 1, 0.35 ≤ h ≤ 0.55, 0.40 ≤ i ≤ 0.55, 0 < j ≤ 0.1, 0 < k ≤ 0.05; the third sub-coating contains nanocrystalline TiAlBN and amorphous SiB m N n ; The first gradient layer is a TiAlSiN layer, wherein the Si content in the first gradient layer increases gradually from the inside to the outside and is not higher than the Si content in the second sub-coating layer; The second gradient layer is a TiAlSiBN layer, wherein the content of B in the second gradient layer increases gradually from the inside to the outside and is not higher than the content of B in the third sub-coating layer; The coating is deposited by a chemical vapor deposition method; the critical load Lc of the bonding strength of the coating is ≥107N, and the absolute value of the residual stress is >1500MPa.
2. The cutting tool with a high-hardness self-lubricating coating according to claim 1, characterized in that: The second sub-coating layer comprises face-centered cubic phase fcc-TiN, face-centered cubic phase fcc-AlN, close-packed hexagonal phase hcp-AlN and amorphous phase a-Si3N4, wherein the volume fraction of the face-centered cubic phase fcc-AlN is not less than 60%.
3. The cutting tool with a high-hardness self-lubricating coating according to claim 1, characterized in that: The Ti / Al atomic ratio in the second sub-coating is 0.5~1.
3.
4. The cutting tool with a high-hardness self-lubricating coating according to claim 1, characterized in that: The third sub-coating is amorphous SiB m N n The morphology of encapsulated nanocrystalline TiAlBN coexists, wherein the grain size of the nanocrystalline TiAlBN is ≤30nm.
5. The cutting tool with a high-hardness self-lubricating coating according to claim 1, characterized in that: The total thickness of the coating is 6~25μm; the thickness of the first sub-coating is 3~8μm; the thickness of the second sub-coating is 1~5μm; the thickness of the third sub-coating is 1~5μm; the thickness of the first gradient layer and the second gradient layer are both 0.5~2μm.
6. The cutting tool with a high-hardness self-lubricating coating according to claim 1, characterized in that: The coating also includes a primer layer adjacent to the surface of the tool substrate and an outermost colored layer, wherein the primer layer and the colored layer are respectively composed of at least one of Ti, TiN, TiC, and TiCN, wherein the thickness of the primer layer is 0.1-0.5 μm, and the thickness of the colored layer is 0.1-2 μm.
7. A method for preparing a cutting tool having a high-hardness self-lubricating coating according to any one of claims 1 to 6, characterized in that: The steps include: S1: The first sub-coating is obtained by chemical reaction using chemical vapor deposition technology at 700-900°C and 6-20mbar with H2, TiCl4, AlCl3, and NH3 as raw materials; S2: Using chemical vapor deposition technology, at 700-900°C and 6-20 mbar, using H2, TiCl4, SiCl4, AlCl3, and NH3 as raw materials, gradually increasing the flow rate of SiCl4, and obtaining the first gradient layer through chemical reaction; S3: The second sub-coating is obtained by chemical reaction using chemical vapor deposition technology at 700~900℃ and 6~20mbar with H2, TiCl4, SiCl4, AlCl3 and NH3 as raw materials; S4: Using chemical vapor deposition technology, at 700~900℃, 6~20mbar, with H2, TiCl4, SiCl4, BCl3, AlCl3, NH3 as raw materials, Ar as carrier gas, and gradually increasing the flow rate of BCl3, the second gradient layer is obtained by chemical reaction; S5: The third sub-coating is obtained by chemical reaction using chemical vapor deposition technology at 700~900℃ and 6~20mbar with H2, TiCl4, SiCl4, BCl3, AlCl3, NH3 as raw materials and Ar as carrier gas.
Citation Information
Patent Citations
High-temperature-oxidation-resistant and self-lubricating multi-layer coating cutter and preparation method thereof
CN114672786A
CVD (Chemical Vapor Deposition) coating cutting tool and preparation method thereof
CN116555725A